The relationship between three measures of L2 vocabulary knowledge and L2 listening and reading. (January 2018) - Cheng, Junyu; Matthews, Joshua
This study explores the constructs that underpin three different measures of vocabulary knowledge and investigates the degree to which these three measures correlate with, and are able to predict, measures of second language (L2) listening and reading. Word frequency structured vocabulary tests tapping receptive/orthographic (RecOrth) vocabulary knowledge, productive/orthographic (ProOrth) vocabulary knowledge and productive/phonological (ProPhon) vocabulary knowledge and tests measuring L2 listening and L2 reading were administered to 250 tertiary-level Chinese learners of English as a foreign language (EFL). Results showed that ProPhon vocabulary knowledge correlated most strongly with L2 listening ( r = .71) and ProOrth vocabulary knowledge correlated most strongly with L2 reading ( r = .57). Factor analysis indicated that all subcomponents of the ProPhon vocabulary knowledge test loaded onto one factor and those of the RecOrth and ProOrth vocabulary knowledge tests loaded onto another. Regression modelling showed that ProPhon vocabulary knowledge explained 51% of the variance in L2 listening scores and that ProOrth vocabulary knowledge explained 33% of the variance in the L2 reading scores. Discussion addresses the varying importance of different dimensions of vocabulary knowledge in L2 listening and reading.